Quantitative metrics for assessing IMRT plan quality: comparing planning conformity and complexity - Soh, Hwee Shin (2018)
Intensity Modulated Radiation Therapy (IMRT) is a complex form of radiation delivery for the treatment of malignant tumours and other diseases. In IMRT treatment planning, quantitative assessment is crucial to measure and improve the plan quality and treatment delivery. The search for simple and universal quantitative metrics to assess IMRT treatment plan quality has been identified as important but as yet not entirely successful. The aim of this thesis was to assess the IMRT treatment plan quality by establishing quantitative metrics for planning conformity and complexity. The metrics proposed in this work were simple, reproducible and universally applicable to all IMRT techniques, which included step-and-shoot IMRT (SSIMRT), volumetric modulated arc therapy (VMAT) and helical tomotherapy (HT).